Comparison of sonographic and cytological diagnoses of solid thyroid nodules: Emphasis on the discordant cases. Issue 12 (21st September 2015) - Lee, Yoo Jin; Kim, Dong Wook; Park, Young Mi; Park, Ha Kyoung; Jung, Soo Jin; Kim, Do Hun; Lee, Seok Mo; Oh, Minkyung
Abstract : Background: This study aimed to assess solid thyroid nodule (STN) cases with discordant sonographic and cytological diagnoses and to compare the diagnostic indices of these modalities. Methods: From January 2013 to December 2013, a single radiologist performed consecutive thyroid ultrasonography (US) and US‐guided fine‐needle aspiration (US‐FNA) to diagnose 347 STNs in 347 patients. Each STN was classified into 1 of 5 categories according to the US diagnosis before US‐FNA: "benign, " "probably benign, " "indeterminate, " "suspicious for malignancy, " or "malignant." We assessed cases where the sonographic and cytological STN diagnoses were discordant, using the final diagnosis as the reference standard. Results: Of the 347 STNs, 279 (80.4%) had a final diagnosis confirmed. The "benign, " "probably benign, " and "malignant" US categories showed high concordance with the cytological diagnoses, whereas the "suspicious for malignancy" US category revealed only a 62.2% concordance rate. The prevalence of indeterminate cytology was higher in the "indeterminate" and "suspicious for malignancy" US categories than other US categories. STNs with indeterminate cytology showed a higher malignancy rate in the malignant US categories. When STNs classified into indeterminate categories from the sonographic (n = 49) and cytological (n = 18) diagnoses were excluded, the sensitivity, specificity, and accuracy of the sonographic and cytological diagnoses were 95.5 and 98.8%, 92.1 and 100%, and 93.0 and 99.6%, respectively. Conclusion: The "suspicious for malignancy" US category showed higher discordance with cytological diagnoses than other US categories, and the diagnostic value of US was lower than that of cytology. Diagn. Cytopathol. 2015;43:953–959. © 2015 Wiley Periodicals, Inc.